Epithelial-Mesenchymal Transition Promotes the Differentiation Potential of Xenopus tropicalis Immature Sertoli Cells - Nguyen, Thi Minh Xuan; Vegrichtova, Marketa; Tlapakova, Tereza; Krulova, Magdalena; Krylov, Vladimir (Stem cells international, 2019)
Epithelial-mesenchymal transition (EMT) is a fundamental process in embryonic development by which sessile epithelial cells are converted into migratory mesenchymal cells. Our laboratory has been successful in the establishment of Xenopus tropicalis immature Sertoli cells (XtiSCs) with the restricted differentiation potential. The aim of this study is the determination of factors responsible for EMT activation in XtiSCs and stemness window acquisition where cells possess the broadest differentiation potential. For this purpose, we tested three potent EMT inducers-GSK-3 inhibitor (CHIR99021), FGF2, and/or TGF-β1 ligand. XtiSCs underwent full EMT after 3-day treatment with CHIR99021 and partial EMT with FGF2 but not with TGF-β1. The morphological change of CHIR-treated XtiSCs to the typical spindle-like cell shape was associated with the upregulation of mesenchymal markers and the downregulation of epithelial markers. Moreover, only CHIR-treated XtiSCs were able to differentiate into chondrocytes in vitro and cardiomyocytes in vivo. Interestingly, EMT-shifted cells could migrate towards cancer cells (HeLa) in vitro and to the injury site in vivo. The results provide a better understanding of signaling pathways underlying the generation of testis-derived stem cells.